2010
DOI: 10.1038/npp.2010.150
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Oscillatory Power is Impaired During Cognitive Control Independent of Medication Status in First-Episode Schizophrenia

Abstract: Schizophrenia is characterized by impaired cognitive control associated with prefrontal cortex dysfunction, but the underlying pathophysioloical mechanisms remain unknown. Higher cognitive processes are associated with cortical oscillations in the gamma range, which are also impaired in chronic schizophrenia. We tested whether cognitive control-related gamma deficits are observed in firstepisode patients, and whether they are associated with antipsychotic medication exposure. Fifty-three first-episode schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
176
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(183 citation statements)
references
References 63 publications
(73 reference statements)
5
176
1
1
Order By: Relevance
“…The loss of PV corresponds with a pathological alteration in oscillatory activity with broad consequences on network dynamics between brain regions. Gamma oscillations in the HPC require GABA A receptor activity (Whittington et al, 1995), and there is a loss of evoked gamma oscillatory activity, both in MAM rats and in humans, in regions showing PV neuron decreases (Gonzalez-Burgos et al, 2010;Lodge et al, 2009;Minzenberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The loss of PV corresponds with a pathological alteration in oscillatory activity with broad consequences on network dynamics between brain regions. Gamma oscillations in the HPC require GABA A receptor activity (Whittington et al, 1995), and there is a loss of evoked gamma oscillatory activity, both in MAM rats and in humans, in regions showing PV neuron decreases (Gonzalez-Burgos et al, 2010;Lodge et al, 2009;Minzenberg et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests that induced gamma-band activity is reduced during a wide range of cognitive and perceptual paradigms, including working memory, executive control and perceptual processing in both chronic and unmedicated patient populations, suggesting a generalized circuit dysfunction in schizophrenia [31,32]. Finally, reduced auditory evoked 7 activity has been demonstrated in first-degree relatives of patients with schizophrenia as well as in unaffected, monozygotic twins with a high degree of heritability [33,34], suggesting the neural synchrony parameters are endophenotypes.…”
Section: Neural Synchrony and Dysconnectivity In Schizophreniamentioning
confidence: 99%
“…Thus PV cells play a central role in coordinating the activity of excitatory pyramidal cells and GABAergic interneurons governing the synchronisation of cortical gamma-oscillations (Gonzalez-Burgos and Lewis, 2012), and it has been shown that the induction of gamma-oscillations is dependent on NMDARs expressed in PV interneurons (Sohal et al 2009;CarlĂ©n et al 2012). Although the mPFC contains the PV neurons generating and regulating gamma-oscillations and is probably the site important in schizophrenia patients (Beasley and Reynolds, 1997;Danos et al 1998;Zhang and Reynolds 2002;Cho et al 2006;Uhlhaas and Singer 2010;Minzenberg et al 2009Minzenberg et al , 2010) and animal models (Cochran et al 2003;McKibben et al 2010;Thomsen et al 2010), we found no PCPinduced c-Fos-IR in PV-IR cells in the mPFC areas. Consistently, a previous study found no increase in c-Fos mRNA in GABAergic neurons in the mPFC (Santana et al 2011).…”
Section: Pcp-induced C-fos-ir In Gabaergic Interneuronsmentioning
confidence: 99%
“…This increase in PFC activity has been observed to be followed by a delayed depression of activity over a 24 hours period followed (Gao et al 1993(Gao et al , 1998, which may be relevant to the decrease in PFC activity 5 seen in schizophrenia patients. Furthermore, PFC synchronous gamma-oscillations important for cognitive function are impaired in schizophrenia (Cho et al 2006;Uhlhaas and Singer, 2010;Minzenberg et al 2009Minzenberg et al , 2010Gonzalez-Burgos and Lewis, 2012). Importantly, those neurons mediating the psychotomimetic actions of non-competitive NMDAR antagonists are still unknown.…”
Section: Introductionmentioning
confidence: 99%